THE IMPACT OF PANDEMIC ISOLATION ON THE PROCESS OF EDUCATION - Violeta Lyubomirova Georgieva-Hristozova (International Journal of Innovative Technologies in Social Science, 2020)
This work discusses the problems of modern education due to the social and economic impact of COVID-19 on society, and it is an attempt to describe the new reality for many educators, along with prescriptions for mitigating the overall burden on the education process by imposing specific national and European policies. The theoretical narrative aims at informing the researchers in the area of education, as well as teachers, educators and to expand the horizons of many students, explicitly majoring in early education and pedagogy on important current topics of modern culture.